Calcium Flux across Plant Mitochondrial Membranes: Possible Molecular Players - Carraretto, Luca; Checchetto, Vanessa; De Bortoli, Sara; Formentin, Elide; Costa, Alex; Szabó, Ildikó; Teardo, Enrico (Frontiers in Plant Science, 2016)
Plants, being sessile organisms, have evolved the ability to integrate external stimuli into metabolic and developmental signals. A wide variety of signals, including abiotic, biotic, and developmental stimuli, were observed to evoke specific spatio-temporal Ca2+ transients which are further transduced by Ca2+ sensor proteins into a transcriptional and metabolic response. Most of the research on Ca2+ signaling in plants has been focused on the transport mechanisms for Ca2+ across the plasma- and the vacuolar membranes as well as on the components involved in decoding of cytoplasmic Ca2+ signals, but how intracellular organelles such as mitochondria are involved in the process of Ca2+ signaling is just emerging. The combination of the molecular players and the elicitors of Ca2+ signaling in mitochondria together with newly generated detection systems for measuring organellar Ca2+ concentrations in plants has started to provide fruitful grounds for further discoveries. In the present review we give an updated overview of the currently identified/hypothesized pathways, such as voltage-dependent anion channels, homologs of the mammalian mitochondrial uniporter, LETM1, a plant glutamate receptor family member, adenine nucleotide/phosphate carriers and the permeability transition pore, that may contribute to the transport of Ca2+ across the outer and inner mitochondrial membranes in plants. We briefly discuss the relevance of the mitochondrial Ca2+ homeostasis for ensuring optimal bioenergetic performance of this organelle.